Direct Reprogramming of Adult Human Somatic Stem Cells Into Functional Neurons Using Sox2, Ascl1, and Neurog2 - Araújo, Jessica Alves de Medeiros; Hilscher, Markus M.; Marques-Coelho, Diego; Golbert, Daiane C. F.; Cornelio, Deborah A.; Batistuzzo de Medeiros, Silvia R.; Leão, Richardson N.; Costa, Marcos R. (Frontiers in Cellular Neuroscience, 2018)
Reprogramming of somatic cells into induced pluripotent stem cells (iPS) or directly into cells from a different lineage, including neurons, has revolutionized research in regenerative medicine in recent years. Mesenchymal stem cells are good candidates for lineage reprogramming and autologous transplantation, since they can be easily isolated from accessible sources in adult humans, such as bone marrow and dental tissues. Here, we demonstrate that expression of the transcription factors (TFs) SRY (sex determining region Y)-box 2 (Sox2), Mammalian achaete-scute homolog 1 (Ascl1) or Neurogenin 2 (Neurog2) is sufficient for reprogramming human umbilical cord mesenchymal stem cells (hUCMSC) into induced neurons (iNs). Furthermore, the combination of Sox2/Ascl1 or Sox2/Neurog2 is sufficient to reprogram up to 50% of transfected hUCMSCs into iNs showing electrical properties of mature neurons and establishing synaptic contacts with co-culture primary neurons. Finally, we show evidence supporting the notion that different combinations of TFs (Sox2/Ascl1 and Sox2/Neurog2) may induce multiple and overlapping neuronal phenotypes in lineage-reprogrammed iNs, suggesting that neuronal fate is determined by a combination of signals involving the TFs used for reprogramming but also the internal state of the converted cell. Altogether, the data presented here contribute to the advancement of techniques aiming at obtaining specific neuronal phenotypes from lineage-converted human somatic cells to treat neurological disorders.